Electric distribution systems - Sallam, A. A. (Abdelhay A.); Malik, Om P. (Piscatawy, NJ : IEEE Press ; Hoboken, New Jersey : Wiley, 2011)
"Electricity distribution is the penultimate stage in the delivery of electricity to end users. The only book that deals with the key topics of interest to distribution system engineers, Electric Distribution Systems presents a comprehensive treatment of the subject with an emphasis on both the practical and academic points of view. Reviewing traditional and cutting-edge topics, the text is useful to practicing engineers working with utility companies and industry, undergraduate graduate and students, and faculty members who wish to increase their skills in distribution system automation and monitoring."--
"A comprehensive treatment of electric distribution systems is given in the book. Although a few books that cover specific topics in more depth are available, there is hardly any book that deals with the key topics of interest to distribution system engineers. It introduces these topics from two points of view: 1- The practical point of view by providing practical examples and the problems which can be met. 2- The academic point of view where the analysis and various techniques used for distribution system planning are explained. Therefore, the major outstanding feature of this book is a combination of practical and academic explanation of its contents. Another outstanding feature is a collection of the traditional and recent topics of distribution systems in one book"--
PART V. DISTRIBUTED GENERATION. CHAPTER 14. DISTRIBUTED GENERATION. 14.1. Power Systems and Distributed Generation (DG). 14.2. Performance of Distributed Generators. 14.3. Case Study.
Series numbering from title page verso CIP.
Includes bibliographical references (pages 537-548) and index.
Online resource and print version record. Title from PDF title page, IEEE Xplore (viewed April 16, 2015).
Keywords: Electric power distribution; Electric power distribution; TECHNOLOGY & ENGINEERING -- Electrical; Electric power distribution; Electronic books; Electronic books; Electronic books